Effects of injection timing and compression ratio on the combustion performance and emissions of a two-stroke DISI engine fuelled with aviation kerosene. (October 2019) - Ning, Le; Duan, Qimeng; Wei, Yuhao; Zhang, Xin; Yu, Kang; Yang, Bo; Zeng, Ke
Highlights: Two-stroke SI engine fueled with RP-3 under knock limited condition was studied. Performance of gasoline and RP-3 in a two stroke DISI engine were compared. Effects of injection timing and compression ratio were investigated and studied. Abstract: In recent years, many civilian and military unmanned aerial vehicles (UAVs) have been powered by spark ignition (SI) piston engines fuelled with gasoline. However, the safety problems associated with the storage and transportation of gasoline are forcing manufacturers and researchers to develop an SI piston engine fuelled with heavy fuel, such as light diesel or aviation kerosene. In this study, the effects of injection timing and compression ratio on the combustion characteristics and emissions of a two-stroke engine fuelled with aviation kerosene rocket propellant 3 (RP-3) are investigated. The engine tests were carried out on a two-stroke, air cooled, direct injection, spark ignition engine at three compression ratios (7.2, 6.2, and 5.2) and injection timings from 120° crank angle (CA) before top dead center (BTDC) to 240° CA BTDC. The engine was run at 4000 rpm, 100% throttle opening, and spark timing at knock limited spark advance. The results showed that the brake power (BP) increased and the coefficient of variation of the indicated mean effective pressure (COVIMEP ) decreased with the advance in injection timing. The best brake thermal efficiency (BTE) was obtained at a direct injection timing of 150 °CA BTDC. Hydrocarbon (HC) and nitric oxide (NO) emissions increased while carbon monoxide (CO) emission decreased as the direct injection timing advanced. The compression ratios were decreased from 7.2 to 5.2, and the maximum values of BP and BTE were obtained at the compression ratio of 6.2. However, the HC and NO emissions at the compression ratio of 6.2 were greater than those under other compression ratios.